Fuera, Hombre Mosca! - Arnold, Tedd.; Geada, Karina (New York : Scholastic, 2011)
A pet fly searches for his favorite brown, oozy, lumpy, smelly food.
"Scholastic en espanol" -- Cover.
"This edition is available for distribution only through the school market"--P. [4] of cover.
Keywords: Flies -- Juvenile fiction; Spanish language materials